Impact on Primary Care Access Post-Disaster: A Case Study From the Rockaway Peninsula. (11th May 2016) - Sood, Rishi K.; Bocour, Angelica; Kumar, Supriya; Guclu, Hasan; Potter, Margaret; Shah, Tanya B.
ABSTRACT: Objective: Assess Hurricane Sandy's impact on primary care providers' services in the Rockaways. Methods: In-person surveys were conducted in 2014. A list of 46 health care sites in the area of interest was compiled and each site was called to offer participation in our survey. Respondents included physicians and practice administrators who remained familiar with Sandy-related operational challenges. Results: Of the 40 sites that opted in, most had been in their current location for more than 10 years (73%) and were a small practice (1 or 2 physicians) before Hurricane Sandy (75%). All but 2 (95%) had to temporarily close or relocate. All sites experienced electrical problems that impacted landline, fax, and Internet. Less than one-quarter (n = 9) reported having a plan for continuity of services before Hurricane Sandy, and 43% reported having a plan poststorm. The majority (80%) did not report coordinating with other primary care stakeholders or receiving support from government agencies during the Sandy response. Conclusions: Hurricane Sandy significantly disrupted access to primary care in the Rockaways. Severe impact to site operations and infrastructure forced many practices to relocate. Greater emergency response and recovery planning is needed, including with government agencies, to minimize disruptions of access to primary care during disaster recovery. ( Disaster Med Public Health Preparedness . 2016;10:492–495)